Wideband Continuous-time [sigma][delta] ADCs, Automotive Electronics, and Power Management : Advances in Analog Circuit Design 2016 - Baschirotto, A.; Harpe, Pieter; Makinwa, Kofi A. A. (Springer, 2016)
This book is based on the 18 tutorials presented during the 25th workshop on Advances in Analog Circuit Design. Expert designers present readers with information about a variety of topics at the frontier of analog circuit design, including low-power and energy-efficient analog electronics, with specific contributions focusing on the design of continuous-time sigma-delta modulators, automotive electronics, and power management. This book serves as a valuable reference to the state-of-the-art, for anyone involved in analog circuit research and development.
Keywords: Analog integrated circuits -- Congresses.; Broadband communication systems -- Congresses.; Motor vehicles -- Electronic equipment -- Congresses.; Electric power systems -- Management -- Congresses.; elektronické knihy; electronic books